‘You can never cross the same river twice’: climbers’ embodied quests for ‘original adventure’ in southern Thailand - Bott, Esther (Sage, 2015)
This article presents ethnographic research into individual narratives of adventure in a small, undeveloped bay called Ton Sai in southern Thailand’s Krabi Province. Ton Sai is extremely popular with Western rock climbers and increasingly with other adventure seekers and backpackers questing for ‘authentic’ Thailand, yet is subject to almost no representation in the commercial sense. It is an example of a destination that is not on the corporate ‘radar’, yet, as will be seen, is famed, desired and produced by ‘niche’ tourists seeking very specifically valued tropical adventures. This research aims to interrogate how such a destination becomes, and remains, valued as adventurous by climbers and therefore shed some light on individual, subjective production of adventure in specific Developing World contexts. Drawing on original interview and other ethnographic data collected during winter 2012/2013, this article argues that even when third-party commercial mediators are absent, the powers of quest for authenticity and adventure are powerful enough to turn the wheels of mediation themselves. In the ‘elite circles’ in which this group manoeuvres, notions of ideal adventure space run deep and are reproduced discursively and through embodied performances in an exoticised environment that is valued for its ‘primitive timelessness’. The implications of this for locals are explored.